Determination of the p-monochlorophenol residue in the calcium hydroxide plus p-monochlorophenol combination used as an intracanal dressing in pulpless teeth of dogs with induced chronic periapical lesion - Alencar, A. H. G.; Leonardo, M. R.; Silva, L. A. B.; Silva, R. S.; Ito, I. Y. (Williams & Wilkins, 1997)
To determine the presence of p-monochlorophenol in the calcium hydroxide (Calen) + p-monochlorophenol combination after its use as intracanal dressing, periapical lesions were induced in 60 root canals of upper and lower premolars of four dogs, After biomechanical preparation, the root canals received the intracanal medication, which was removed from the apical third after 2, 4, 7, and 14 days for chemical analysis by spectrophotometry, the results showed a p-monochlorophenol loss of approximately 50.0% in the dressing after 48 h, with no further significant loss after longer periods of times, p-Monochlorophenol was still present in the medication after 14 days.